Antecedente nacional e internacional sobre la percepción y los derechos de las niñas, los niños, los y las adolescentes - Vicente Salazar, Rodolfo (2008)
Until the middle of the XVIII Century, children were considered as miniature adults, but with Jean Jacob Rousseau the study of the development of the human being was started and the foundation was set up for the new science of Paidology (the study of children), wich focuses on the different intellectual and physical conflicts which children face, and also for other sciencies such as Paidofilaxis, Pueroculture and Pediatrics. The Society of Nations, created, in 1919, the Consultancy for the Trafficking of Women and the Protection of Children, and in Geneva, the International Union for Aid was founded in 1920. In Argentina, the First American Congress for Children was organized in 1916, and others followed. The first Declaration of Childrens Right was proclaimed in 1924 and then followed the first Ten Commandments of Childrens Rights. In Costa Rica in 1929, a project was presented for the Constitutional Congress to establish an institution for the protection of children, wich was duly enacted into law in 1930 with the name of National Institution for the Protection of Children (Patronato Nacional de la Infancia, PANI) whose duty was to oversee the welfare of minors and their physical, intellectual, moral and emotional development. In 1930, the first Declaration of the Rights for Costarrican Children was proclaimed. The creation of the PANI, the declaration of Childrens Rights, and the enactment of a Code for Infants (1932), constitute the three events that signal Costa Rica as one of the pioneers countries in Latin American and the World, in the protectionof children and mothers. At the end of the article, some of the crucial events that have happened during the decades that PANI has been working in the country are analized.